2021
DOI: 10.1016/j.compeleceng.2021.107268
|View full text |Cite
|
Sign up to set email alerts
|

Using a digital whiteboard for student engagement in distance education

Abstract: The COVID-19 pandemic transformed educational processes across different educational levels. As institutions and faculty members effort focused on guaranteeing academic continuity, the challenge was how to translate the learning methodologies applied in the classroom to virtual settings. A digital whiteboard was integrated to synchronous class sessions to complement the educational experience. During these sessions, students and teachers interacted to co-construct ideas and socialize learning. The objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 10 publications
0
19
0
4
Order By: Relevance
“…There are studies, where authors underline that their approach consisted of not just making available other materials for students to use online during the Covid-19 period (Klein et al, 2019). Although in a remote model of the practical classes tutors should understand that the preparation of the students is important in the dynamic development of the study course (Reguera & Lopez, 2021). Tutors should consider students as the main persons in the practical classes while the tutors themselves play the leading role in the process of "teach by learning and research by teaching" (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There are studies, where authors underline that their approach consisted of not just making available other materials for students to use online during the Covid-19 period (Klein et al, 2019). Although in a remote model of the practical classes tutors should understand that the preparation of the students is important in the dynamic development of the study course (Reguera & Lopez, 2021). Tutors should consider students as the main persons in the practical classes while the tutors themselves play the leading role in the process of "teach by learning and research by teaching" (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…During the current period of the COVID-19 pandemic, there are already studies that have been conducted on student engagement in the HE sector. Examples of these studies are those by Chen., Kaczmarek, and Ohyama (2020); Dahleez et al (2021); Hewson and Chung (2021) and Reguera and Lopez (2021). For instance, the study by Chen et al (2020) investigated student engagement together with the learning outcomes and students' perceptions of an online course that incorporated quizzes, tasks and tests as a formative assessment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The consequences showed that scholars enjoyed the dynamic (four.Fifty six) and college students believed that the integration of the digital whiteboard contributed (4.72) to their knowledge of abstract principles (4.Eighty three). Designing instructional programs that comprise those sources translates into energetic studying dynamics that foster scholar engagement [9]. This architectural development coincided with swiftly-evolving branch-huge technological advances that challenged traditional teaching techniques at this faculty.…”
Section: Digital Whiteboard Foster Student Engagementmentioning
confidence: 99%